Seeing Otherwise: ‘The Least of These’ and Revelation in Jean-Luc Marion - Breedlove, Thomas (Heythrop journal, 2025)
In his familiar essay in Phenomenology and the ‘Theological Turn’, Jean-François Courtine writes that the ‘cardinal experience’ of revelatory phenomena would undoubtedly be the incarnation. But in its singularity, this experience, he admits, seems to elude phenomenological thought. Against such a judgement, many Christian traditions affirm Christ's ongoing presence in diverse privileged sites, in the eucharist, saints, the Church itself, and, via Christ's own identification with ‘the least of these’ in Matthew's parable, in those who suffer. This essay considers this last possibility of divine manifestation, taking up ‘the least of these’ to reconsider the relationship between finitude and the infinite in Jean-Luc Marion's phenomenogical account of revelation and saturation. While the heart of Marion's account, both in his words and according to his critics, has primarily concerned revelation's contradiction of finite experience, this essay argues that the development of Marion's own hermeneutics and his attentiveness to paradox and kenosis also reveal the confirmation of finitude at the heart of revelation. Revelation, that is, though it comes from elsewhere, is not other than finitude, but finitude otherwise, finitude's transfiguration.